Pengaruh Jiwa Kewirausahaan dan Inovasi terhadap Keterlibatan Pegawai dengan Pengembangan Karir sebagai Moderasi pada Badan Kepegawaian Daerah (BKD) Provinsi Jambi - Martasudira, Yosse; Lubis, Tona Aurora; Masriani, Ida (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the influence of entrepreneurial spirit and innovation on employee engagement with career development as a moderating variable in the Regional Civil Service Agency (BKD) of Jambi Province. This study uses a quantitative approach with an explanatory method to explain the causal relationship between variables. Primary data were collected through questionnaires distributed to all BKD employees using the total sampling technique. Data analysis was carried out using the partial least square (PLS) method. The results of the study indicate that entrepreneurial spirit as measured by indicators of self-confidence, full initiative, orientation to results, leadership, and courage to take risks, does not have a significant effect on employee engagement. In contrast, innovation as measured by indicators of new processes, investment in training and development, participation, ideas implemented, and level of collaboration, has a positive and significant effect on employee engagement. However, career development variables reflected by organizational policies, work performance, work experience, and flexibility in socializing are unable to moderate the relationship between entrepreneurial spirit and innovation on employee engagement. This means that innovation has an important role in increasing employee engagement, while career development requires adjustments to be more relevant to employee needs.